Street Food Vending and Hygiene Practices and Implications for Consumers - Kok, R. (Journal of Economics and Behavioral Studies, 2014)
Street food vending has and is becoming globally a convenient and in most cases an essential service. Lifestyle changes and socio economic factors creates very little space for consumers to look at other alternatives one of which would be to prepare one’s own meal. Street food therefore becomes an easy and economic means to acquire prepared food. Safe hygiene practices should become integral to the vendor as the product will be consumed by people of all ages and many may be vulnerable to poor quality food. The street food vendor in turn relies on this service as a means of employment and income generation. The competition between vendors is increased and the pressure to cut corners becomes a reality and one significant corner is appropriate hygiene practices. The practice of appropriate hygiene practices is also as a result of total ignorance of many vendors and the nature of the food that they prepare. The paper explores lessons from various countries in respect of dealing with ensuring good hygiene practices of street food vendors and its usefulness to the South African perspective. One such initiative is the programme launched by the India’s Food Safety and Standards Authority and the National Association of Street Vendors of India. South African street food industry is rapidly increasing in size and proportion. Several studies have been undertaken to look at this operation from various perspectives including hygiene practices and small business. Employment creation has become a national imperative of the country and small business development is seen as a significant component to employment creation. This paper sets out to establish the global practices in street food vending from a hygiene perspective and its relevance to the South African context.